1989
DOI: 10.1002/syn.890040409
|View full text |Cite
|
Sign up to set email alerts
|

D1 dopamine receptor stimulation enables the postsynaptic, but not autoreceptor, effects of D2 dopamine agonists in nigrostriatal and mesoaccumbens dopamine systems

Abstract: Possible functional interactions between D1 and D2 dopamine (DA) receptors were examined using extracellular single-cell recording with microiontophoretic application of selective D1 and D2 receptor agonists both postsynaptically, in the rat nucleus accumbens (NAc) and caudate-putamen (CPu), and presynaptically, at impulse-regulating somatodendritic DA autoreceptors in the ventral tegmental area (A10) and substantia nigra pars compacta (A9). In addition, synthesis-modulating nerve terminal DA autoreceptors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 108 publications
10
69
1
Order By: Relevance
“…Thus, disinhibition of the striatopallidal pathway induced by D 2 receptor blockade may require functional D 1 receptors. The finding that excitation of pallidal neurons induced by D 2 agonists (via inhibition of the striatopallidal projection) is impaired reducing striatal D 1 receptor occupancy (Walters et al 1987;Wachtel et al 1989) further supports this view.…”
Section: )mentioning
confidence: 62%
“…Thus, disinhibition of the striatopallidal pathway induced by D 2 receptor blockade may require functional D 1 receptors. The finding that excitation of pallidal neurons induced by D 2 agonists (via inhibition of the striatopallidal projection) is impaired reducing striatal D 1 receptor occupancy (Walters et al 1987;Wachtel et al 1989) further supports this view.…”
Section: )mentioning
confidence: 62%
“…Previous studies have demonstrated cooperativity between D1 and D2 receptors (White, 1987;Wachtel et al, 1989;Keefe and Gerfen, 1995). At "normal", i.e., basal, DA concentrations, D2 autoreceptors may mediate the inhibition of DA neurons.…”
Section: Discussionmentioning
confidence: 97%
“…For example, both pharmacological blockade and gene knock-out of the dopamine D 1 receptor attenuated the physiological effects of dopamine and D 1 -and D 2 -selective agonists Clark and White, 1987;Walters et al, 1987;White et al, 1988;Wachtel et al, 1989;Johansen et al, 1991;Xu et al, 1994a,b;Cooper et al, 1998;Waszczak et al, 2002). Conversely, D 1 stimulation enabled the full expression of behavioral effects and molecular and cellular adaptations induced by dopamine indirect and direct D 1 and D 2 agonists White et al, 1988;Xu et al, 1994a,b;Gerfen et al, 1995;Keefe and Gerfen, 1995;Xu et al, 2000;RalphWilliams et al, 2002;Waszczak et al, 2002;Fetsko et al, 2003;Zhang et al, 2004;Ralph and Caine, 2005;Zhang et al, 2005;Zhang et al, 2006).…”
Section: A Permissive Role For D 1 Receptors In the Effects Of Dopamimentioning
confidence: 99%